PENERAPAN METODE PARAMETRIK PADA PERANCANGAN TAMAN ICHARIBA CHODE UNTUK MENGHADIRKAN DWELLING BAGI LANSIA - Bellinda Juniaty Halomoan; Suwardana Winata (Jurusan Arsitektur dan Perencanaan, 2021)
The aging population is a phenomenon that will occur in 2020-2060 due to a decrease in the number of births and an increase in life expectancy. Jakarta as the capital city of Indonesia is predicted to have an increase in the elderly population from 8.47% (2015) to 21.79% (2045). This leads to speculation that senior- friendly housing complexes will emerge in the next 20-30 years. Ichariba Chode Park is designed to keep Elderly active and productive, so they can enjoy retirement with Independence. Because upon entering senior years, people experience a decrease in physical abilities. It may lead to isolation, even loneliness from the surrounding communities. The data collection method is both Qualitative & Quantitative Observation of Longevity-related Documentaries and Journal. Data Procession Method based on Problem Seeking: An Architectural Programming Primer then designed into form With Parametric Design Method; As a result, Ichariba Chode Park emerges as a Leisure Park designed with the following stages: 1. Floor plan designed to accommodate Movement for Elderly, 2. Zoning designed to be Intergeneration Friendly, 3. Solid Void of the massing is designed to incorporate Light, Water, and Nature, 4. The facade is designed regarding color, mass composition, and material. In conclusion, within an urban scale Ichariba Chode Park serves as a Leisure Park that promotes dwelling for elderly. Using Data Procession Method, the designer seek Building Function, Site Location, and Program. While using Parametric Design Method helps the designer to apply design parameters into Floor plan, Section Plan, and Facade. Keywords: Dwellingl Elderly; Intergeneration; Leisure Park; Parametrik AbstrakAging Population merupakan sebuah fenomena yang akan terjadi pada tahun 2020-2060 karena penurunan jumlah kelahiran serta peningkatan angka harapan hidup. Jakarta sebagai Ibukota Indonesia diprediksi mengalami peningkatan jumlah Lansia dari 8.47% (2015) ke 21.79% (2045). Sehingga akan muncul kompleks-kompleks perumahan ramah lansia dalam kurun waktu 20 sampai 30 tahun ke depan. Proyek Taman Ichariba Chode ini dirancang untuk menjaga lansia tetap aktif, produktif, dan menjalani masa pensiunnya dengan independen. Ini dikarenakan Lansia kerap mengalami penurunan kemampuan fisik, yang kerap menimbulkan rasa terisolasi dan kesepian pada komunitasnya. Metode pengumpulan data secara kualitatif dan kuantitatif terhadap Dokumentasi dan Jurnal Ilmiah tentang Lanjut Usia. Metode Pengolahan Data didasari literatur Problem Seeking: An Architectural Programming Primer dan Perancangan menggunakan Parametrik, yaitu membedah data kepada beberapa parameter desain. Hasil akhir yaitu Leisure Park yang di desain dengan tahapan sebagai berikut: 1. Perancangan Denah dengan parameter Movement for Elderly, 2. Perancangan zoning dengan parameter Intergeneration, 3. Perancangan solid void potongan dengan parameter Light, Water, and Nature, dan 4. Perancangan fasad dengan parameter color, mass composition, and material. Kesimpulannya, Taman Ichariba chode berfungsi sebagai Leisure Park yang menghadirkan dwelling bagi para lansia. Menggunakan pengolahan data Perancang mendapatkan Fungsi bangunan, Lokasi Tapak, dan Program. Lalu menggunakan Metode Perancangan Parametrik, Kriteria yang mendukung fisiologi lansia diaplikasikan dalam Denah, Tampak, dan Potongan.